Quantifying the effect of isoflurane and nitrous oxide on somatosensory-evoked potentials - Devadoss, Usha (Medknow Publications, 2010)
Anaesthetic techniques may have a significant effect on intraoperative-evoked potentials (EP). The present study is designed to compare Propofol anaesthesia with Isoflurane (with or without nitrous oxide) during intraoperative somatosensory-evoked potential (SSEP) monitoring in 15 ASA Grade I and II patients undergoing surgery for intracranial tumours. SSEPs in response to median and posterior tibial nerve stimulation were recorded under four different anaesthetic conditions: 1) Propofol infusion and ventilation with air-oxygen, 2) Isoflurane, 1.0 MAC and ventilation with air-oxygen, 3) Isoflurane 1.0 MAC and ventilation with nitrous oxide-oxygen, and 4) Return to Isoflurane, 1.0 MAC and ventilation with air-oxygen. Intraoperative monitoring of somatosensory evoked potentials is best recordable using Propofol. The morphology of the EP is reproducible with Isoflurane. This effect is exaggerated when it is advisable to avoid nitrous oxide.